Predictors of Heavy Episodic Drinking and Weekly Drunkenness Among Immigrant Latinos in North Carolina. (July 2014) - Daniel-Ulloa, Jason; Reboussin, Beth A.; Gilbert, Paul A.; Mann, Lilli; Alonzo, Jorge; Downs, Mario; Rhodes, Scott D.
Few studies have examined correlates of heavy drinking among rural immigrant Latino men. This analysis identified correlates of typical week drunkenness and past 30-day heavy episodic drinking, within a sample of immigrant Latino men in rural North Carolina ( n = 258). In the bivariate analyses, Mexican birth, entering the United States as an adult, and year-round employment were associated with increased odds of typical week drunkenness, and higher acculturation and affiliation with a religion with strict prohibitions against drinking alcohol were associated with lower odds of typical week drunkenness. Being older, Mexican birth, entering the United States as an adult, and lower acculturation were associated with increased odds of heavy episodic drinking, and affiliation with a religion with strict prohibitions against drinking alcohol and completing high school were associated with decreased odds of heavy episodic drinking. In multivariable modeling, only religious affiliation was associated with typical week drunkenness. Mexican birth, entering the United States as an adult, and lower acculturation were associated with increased odds of heavy episodic drinking, and affiliation with a religion with strict prohibitions against drinking alcohol and completing high school were associated with lower odds of heavy episodic drinking. The health of minority men in the United States has been neglected, and immigrant Latino men comprise a particularly vulnerable population. This analysis provides initial data on some factors associated with heavy drinking within a population about which little is known. Future studies should examine moderating or mediating factors between age, acculturation, religiosity, and heavy drinking that might be targets for behavioral interventions.